Dysregulation of Circulating FGF19 and Bile Acids in Primary Biliary Cholangitis-Autoimmune Hepatitis Overlap Syndrome. (12th June 2020) - Li, Zhanyi; Liu, Yu; Yang, Fangji; Pang, Jiahui; Wu, Yuankai; Chong, Yutian; Li, Xiangyong
Abstract : Background . Primary biliary cholangitis-autoimmune hepatitis overlap syndrome (PBC-AIH OS), which exhibits features between autoimmune hepatitis and cholestasis, is a common condition and usually shows a progressive course toward cirrhosis and liver failure without adequate treatment. Synthesis of bile acids (BAs) plays an important role in liver injury in cholestasis, and the process is regulated by fibroblast growth factor 19 (FGF19). The overall role of circulating FGF19 in BA synthesis and PBC-AIH OS requires further investigation. Methods . We analyzed BA synthesis and correlated clinical parameters with serum BAs and FGF19 in 35 patients with PBC-AIH OS. Serum concentrations of 7alpha-hydroxycholest-4-en-3-one (C4) were used to quantify the synthesis of BA directly. Results . Serum FGF19 levels were higher, while C4 levels were substantially lower in PBC-AIH OS patients than those in healthy controls. Circulating FGF19 levels strongly correlated with C4 (r = − 0.695, p < 0.0001 ), direct bilirubin (r = 0.598, p = 0.0001 ), and total bile acids (r = 0.595, p = 0.002 ). Moreover, circulating FGF19 levels strongly correlated with the model for end-stage liver disease score (r = 0.574, p = 0.0005 ) and Mayo risk score (r = 0.578, p = 0.001 ). Conclusions . Serum FGF19 is significantly increased in patients with PBC-AIH OS, while BA synthesis is suppressed. Circulating FGF19 primarily controls the regulation of BA synthesis in response to cholestasis and under cholestatic conditions. Therefore, modulation of circulating FGF19 could provide a promising targeted therapy for patients with PBC-AIH OS.